Motor control, habits, complex motor stereotypies, and Tourette syndrome. (31st October 2013) - Singer, Harvey S.
Abstract : Tourette syndrome (TS) and primary complex motor stereotypies (CMS) are two relatively common, distinctly different movement disorders of childhood. Despite their frequency, the precise underlying pathophysiological mechanism(s) for tics and stereotypies remains unknown. Both are likely to involve cortical–striatal–thalamo–cortical (CSTC) pathways or their interconnecting brain regions. In recent studies, distinct, separate cortical–striatal pathways have been identified for goal‐directed and habitual behavioral activity with important influences from structures, such as the hippocampus, amygdala, dorsolateral prefrontal cortex, cerebellum, ventral tegmental area, and substantia nigra pars compacta. Determining the specific site of abnormality within these circuits remains an active area of research. At the synaptic level, numerous neurotransmitters are involved in the transmission of messages through CSTC pathways, and many have been proposed as potential pathophysiological mechanisms. Which, if any, transmitter is the primary pathological factor in TS and primary CMS remains to be definitively determined.